The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3855/jidc.1816
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with Group A rotavirus infection among children with acute diarrhea in Mwanza, Tanzania

Abstract: Introduction: Rotavirus infections frequently cause acute gastroenteritis in humans and are the most important cause of severe dehydrating diarrhea in young children in both developed and developing countries. Methodology: This was a prospective cross-sectional, hospital-based study on 300 children ≤ 5 years with acute watery diarrhea who attended Bugando Medical Centre (BMC) and Nyamagana District hospital between May and November 2009. Stool specimens were tested for rotavirus infection using latex agglutina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
4
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
5
20
4
6
Order By: Relevance
“…In comparison to other studies done around the world; our findings were similar to studies done in Mali by Ouermi et al [16] and in Tanzania, Mwanza by Temu et al [17] which found prevalence’s of 22.7 and 20.7%, respectively. This similarity could be attributed to the fact that they had the same study duration and both were carried out in hospital settings.…”
Section: Discussionsupporting
confidence: 91%
“…In comparison to other studies done around the world; our findings were similar to studies done in Mali by Ouermi et al [16] and in Tanzania, Mwanza by Temu et al [17] which found prevalence’s of 22.7 and 20.7%, respectively. This similarity could be attributed to the fact that they had the same study duration and both were carried out in hospital settings.…”
Section: Discussionsupporting
confidence: 91%
“…Nausea, place of residence, leukocytosis, and abdominal pain correlated differently with viral and bacterial infections. Many studies have reported that viral pathogens are more likely to be transmitted by person-to-person contact [22][23][24]. Although very few cases were reported to be transmitted by other patients in this study, we found that living in a suburb of Beijing was associated with viral infection.…”
Section: Discussioncontrasting
confidence: 43%
“…The main transmission route of infectious diarrhea is fecal-oral transmission. Consequently, many studies have conducted analytical investigations of dangerous factors to stop this route of transmission (Dennehy, 2000;Nakawesi et al, 2010;Temu et al, 2012;Wilking et al, 2012); relevant factors include dietary habits, the eating environment, food varieties, eating traditions, food storage conditions, and health and economic conditions. However, our long-term clinical observations have demonstrated that some infectious diarrhea cases are not associated with a suspicious food history or unclean dietary habits.…”
Section: Introductionmentioning
confidence: 99%